Números complexos e cônicas : abordagem pelo professor do ensino médio, reflexões e propostas - Santos, Pedro Alexandre Barros (2018)
This dissertation proposes to present an extra tool to be worked with high school students as regards the study of conics, and for that we will use the geometric structures that the complex number of numbers o er mainly when the We use it to represent and classify conics in a reduced way, even when they do not have their axes parallel to the axes of the Cartesian plane. We will also do a case study on the teaching of these contents in high school where we will re ect from the di culties experienced by mathematics teachers in high school.